2012
DOI: 10.1111/j.1755-3768.2012.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab modulates epithelial‐to‐mesenchymal transition in the retinal pigment epithelial cells via connective tissue growth factor up‐regulation

Abstract: ABSTRACT.Purpose: To investigate the effect of bevacizumab treatment on connective tissue growth factor (CTGF) expression and the induction of epithelial-to-mesenchymal transition in ARPE-19 cells and human donor retinal pigment epithelium (HRPE) cells in vitro. Methods: We quantitated the protein and gene expression level of CTGF by ELISA. The effect of Fc-Fc receptor (Fc-FcR) interaction on CTGF expression was evaluated by CD64 siRNA silencing. Expression of epithelial-to-mesenchymal transition markers, alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…This recovered 2 weeks later. Furthermore, cell culture studies suggested anti-VEGF agents cause RPE dedifferentiation (14), reduced barrier function (15), permeability (16), and impaired phagocytosis (17), but have no effect on apoptosis (18). Therefore, complete VEGF inhibition may be detrimental, but given the variability in reported effects, modifying factors could influence patient response and risk of developing side effects.…”
Section: Introductionmentioning
confidence: 99%
“…This recovered 2 weeks later. Furthermore, cell culture studies suggested anti-VEGF agents cause RPE dedifferentiation (14), reduced barrier function (15), permeability (16), and impaired phagocytosis (17), but have no effect on apoptosis (18). Therefore, complete VEGF inhibition may be detrimental, but given the variability in reported effects, modifying factors could influence patient response and risk of developing side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CXCL12 rescued photoreceptors in a model of retinal injury . Uniquely, CTGF was shown to regulate RPE transdifferentiation and cooperate with growth factor signaling for tissue protection in vivo .…”
Section: Resultsmentioning
confidence: 96%
“…Chen et al 41 showed that treatment with bevacizumab induced an epithelial-to-mesenchymal transition in the lineage of human retinal pigment epithelium cells (ARPE 19) by upregulation of the connective tissue growth factor, a profibrotic factor associated with the process of fibrosis. 42 Using the same cell line, Schnichels et al 43 also observed a slightly enhanced effect on cell death after bevacizumab treatment.…”
Section: Discussionmentioning
confidence: 99%